Big snow (The) - Hader, Berta and Elmer (New York : Scholastic Inc, 1990)
"Honk-honk-honk." The wild geese fly south when cold winds begins to blow from the north. The red squirrel stores nuts and acorns and seeds under leaves and logs. It is getting ready for winter. . . and the first BIG SNOW.
Won a Cadecott Medal
Keywords: Snows--Fction; Deers--Fiction; Children stories